The Restorative Justice in Handling Special Criminal Offenses: Between Theory and Practice - Imron Rosyadi (Lembaga Bale Literasi, 2026)
The development of restorative justice as an alternative approach in criminal law has gained increasing attention. However, its application in special criminal offenses remains limited and controversial due to their serious nature and strict legal frameworks. This study aims to analyze the compatibility between the theoretical concept of restorative justice and its practical implementation in handling special criminal offenses, particularly in relation to legal norms and enforcement policies. It also provides a comparative perspective by examining its application in narcotics, corruption, and sexual violence crimes. The research employs a normative juridical method with statute, conceptual, and case approaches, using secondary data from legislation, official policies, and selected court decisions, analyzed descriptively. The findings indicate that although restorative justice is normatively recognized, its implementation remains restricted, selective, and inconsistent. In narcotics cases involving users, it is relatively more applicable through rehabilitation, while in corruption and sexual violence crimes, its application is more limited due to public interest considerations and strict victim protection requirements. This study concludes that these limitations are influenced by rigid legal frameworks and the dominance of punitive approaches, highlighting the need for clearer regulations and adaptive legal policies.